EVALUATING THE SCHOOL LITERACY MOVEMENT PROGRAM THROUGH THE CIPP MODEL: EVIDENCE FROM STATE JUNIOR HIGH SCHOOL 1 SEMANU, INDONESIA - Utami Dwi Ratna Asih; Victor Novianto; Esti Setiawati; Sukadari Sukadari (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aims to: (1) describe the context that underpins the implementation of the school literacy  movement program at State Junior High School 1 Semanu, including policies, needs, and program objectives; (2) analyze the inputs supporting the implementation of the school literacy  movement program, including human resources, facilities and infrastructure, funding, and strategies used; (3) evaluate the process of the school literacy  movement program, including planning, implementation, as well as monitoring and follow-up mechanisms; (4) assess the products or outcomes of the school literacy  movement program, both in terms of students' literacy achievement and its impact on the school's literacy culture; (5) formulate improvement recommendations to enhance the effectiveness of the school literacy  movement program based on the CIPP evaluation model. This study uses a qualitative approach. Data collection techniques include interviews, observation, and document studies. Data validity is tested through source and method triangulation. Data analysis uses the interactive model of Miles and Huberman model which consists of 3 stages, namely: data reduction, data display, and conclusion drawing. In terms of context, the program is already in accordance with policies, needs, and program objectives. In terms of input, resources are available, but facilities and funding are still lacking. In terms of process, most of the program is already running, but it still requires the involvement of all parties. In terms of product, there has been an increase in reading interest and literacy skills, but it is still weak in shaping student character. In conclusion, the program is running well and can be continued with some improvements to operate optimally.